Absorption characteristics and shrinkage mitigation of superabsorbent polymers in pavement concrete. Issue 2 (28th January 2022) - Lyu, Zhenghua; Shen, Aiqin; He, Ziming; Wang, Wenzhen; Mo, Shixiu; Chen, Zhihui; Qin, Xiao
ABSTRACT: To explore the absorption characteristics and swelling behaviour of SAPs under different working conditions of pavement concrete, the optical microscopy was conducted to capture the swelling process during the absorption period. Then, the absorption kinetic parameters were deduced, and swelling models were developed at different working temperatures. Furthermore, the humidity and shrinkage of pavement concrete were monitored synergistically at multiple scales with a cloud signal acquisition system, and the pore structures and hydration products were analysed by mercury intrusion porosimetry (MIP) tests and scanning electron microscopy (SEM) observations. The results show that a relatively high temperature increases the SAP absorption and the absorption rate. The hydrophobic interaction of the SAP groups and the hydrogen bonding between the macromolecular chains alter the time point of the gel phase change. Increasing the temperature accelerates the swelling rate of SAP gel network and increases the SAP absorption. Various water film layers emerge and become narrow within the early transient seconds as the SAP particles begin to crosslink and aggregate. A period of accelerated shrinkage occurs within 100 h in the SAP-pavement panel. At 28 days, SAP increases the concrete porosity but refines the pore structure, and additional hydration products are formed.